2019
DOI: 10.1126/scitranslmed.aau5898
|View full text |Cite
|
Sign up to set email alerts
|

Platelet decoys inhibit thrombosis and prevent metastatic tumor formation in preclinical models

Abstract: Platelets are crucial for normal hemostasis; however, their hyperactivation also contributes to many potentially lethal pathologies including myocardial infarction, stroke, and cancer. We hypothesized that modified platelets lacking their aggregation and activation capacity could act as reversible inhibitors of platelet activation cascades. Here, we describe the development of detergent-extracted human modified platelets (platelet decoys) that retained platelet binding functions but were incapable of functiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
41
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(44 citation statements)
references
References 35 publications
2
41
0
1
Order By: Relevance
“…Cell membrane-coated drug-loaded nanomaterials Good biocompatibility, high drug loading capacity [19][20][21][22] Cell membrane-coated drug-self-assembly nanomaterials [25] Template Cell membrane-coated nanogels Guiding the core formation [27] Nanoreactor Cell membrane-coated a single natural enzyme Improving the stability of enzymes or nanoenzymes in circulation [28,29] Cell membrane-coated a single nanozyme [30] Cell membrane-coated multiple natural enzymes [31,32] Cell membrane-coated multiple nanozymes [33] Cellular communication Circulation Cell membrane-camouflaged polymeric nanomaterials [38,39,43,45] Cell Neutrophil membrane-coated nanomaterials Protection of neutrophils [65] Bacteria membrane-cloaked nanomaterials Protection of body from bacteria adhesion [68] T cell membrane-coated nanomaterials Protection of T cells [69] Targeting Stem cell membrane-coated nanomaterials Enhancing tumor targeting ability [74][75][76][77] Leukocyte membrane-coated nanomaterials [78][79][80][81][82][83][84][85][86][87] Platelet membrane-coated nanomaterials [91,[93][94][95][96][97][98] Tumor cell membrane-coated nanomaterials Homologous targeting ability…”
Section: Selective Permeability Carriermentioning
confidence: 99%
“…Cell membrane-coated drug-loaded nanomaterials Good biocompatibility, high drug loading capacity [19][20][21][22] Cell membrane-coated drug-self-assembly nanomaterials [25] Template Cell membrane-coated nanogels Guiding the core formation [27] Nanoreactor Cell membrane-coated a single natural enzyme Improving the stability of enzymes or nanoenzymes in circulation [28,29] Cell membrane-coated a single nanozyme [30] Cell membrane-coated multiple natural enzymes [31,32] Cell membrane-coated multiple nanozymes [33] Cellular communication Circulation Cell membrane-camouflaged polymeric nanomaterials [38,39,43,45] Cell Neutrophil membrane-coated nanomaterials Protection of neutrophils [65] Bacteria membrane-cloaked nanomaterials Protection of body from bacteria adhesion [68] T cell membrane-coated nanomaterials Protection of T cells [69] Targeting Stem cell membrane-coated nanomaterials Enhancing tumor targeting ability [74][75][76][77] Leukocyte membrane-coated nanomaterials [78][79][80][81][82][83][84][85][86][87] Platelet membrane-coated nanomaterials [91,[93][94][95][96][97][98] Tumor cell membrane-coated nanomaterials Homologous targeting ability…”
Section: Selective Permeability Carriermentioning
confidence: 99%
“…Finally, the creation of modified platelets that retained platelet binding functions but were incapable of functional activation and aggregation, termed "platelet decoys, " led to encouraging results in mouse models, where simultaneous injection of the platelet decoys with tumor cells inhibited metastatic tumor growth (69). The production of reversible drug-free antiplatelet agents by modifying human platelets, is of particular clinical importance as it carries the potential of stopping the formation of metastasis and the burden this is associated with in patients with cancer.…”
Section: Potential Clinical Relevance and Future Perspectivesmentioning
confidence: 99%
“…1A. It will also advance the biocompatibility of new materials for intravascular devices (1), development of 'synthetic' platelets (2) and improve drug delivery (3). Microfluidic channel-based assays for thrombus measurements in vitro typically only quantitate either surface-driven biophysical processes associated with platelet activation and spreading (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…3D), we observed that the magnitude of activity did not increase at all that is indicative of a highly stable basal surface during thrombus formation which is consistent with existing thrombus formation. The full events of platelet spreading and interacting with collagen fiber bundles under fluid shear are shown in Movies S2 and S3.Mapping intra-thrombus stability and adhesive platelet activity inSo far existing high resolution platelet imaging(3,36,37), that has not been able to quantify platelet-platelet activities in entire thrombus and even less is known about the overall impact on the thrombus mass(38). To demonstrate the strength of combinatory labelfree imaging of COSI, we investigate how COSI can extract both the intra-thrombus stability and platelet activity in relation to thrombus embolization (loss of platelet aggregates from the thrombus) as illustrated inFig.…”
mentioning
confidence: 99%